Mitigation of traumatic blepharoptosis with "central levator tuck": A novel approach in upper eyelid repair. Issue 3 (May 2021) - Mehta, Aditi; Thakur, Umang; Saini, Manu; Adiga, Sushant; Grewal, Sartaj Singh; Kashyap, Himanshu; Singh, Simar Rajan; Singh, Manpreet; Pujari, Amar
Purpose: Complex upper eyelid lacerations can present to the emergency department after a myriad of trauma. The goal of the surgical repair is anatomical and functional recovery along with symmetrical cosmesis. Despite meticulous surgery, post traumatic blepharoptosis may develop. We describe an additional step during upper eyelid laceration repair to help mitigate the development of traumatic blepharoptosis. Methods: Patients with traumatic eyelid laceration without head injury, globe injury or associated orbital fractures, who were planned for a primary upper eyelid repair were included. Intraoperatively, wound margins and tissues were identified to establish anatomical continuity. After the LPS muscle was reinserted onto the tarsus, a single, central suture LPS plication – the " central levator tuck " was performed. This helped in improving the muscle action as well as strengthening its reattachment onto tarsus. Results: Four cases underwent laceration repair with this modified technique. The nature of eyelid injury, surgical technique, and the outcome at 6 months is described. Three patients had a successful outcome, whereas one patient developed early scarring which reduced with scar therapy over time. Conclusion: We describe a simple and effective "central levator tuck" technique for traumatic eyelid laceration repair with optimal functional and cosmetic outcome while reducing the development of blepharoptosis in four patients.